2022
DOI: 10.3390/en15197254
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Hybrid Excitation in Electrical Machines

Abstract: Hybrid excitation is a technology that combines the advantages of field windings and permanent magnets for inducing magnetic flux. This article studies the benefits of hybrid excitation and provides an outlook on their possible applications, such as wind power generators and electric vehicle motors. Compared to permanent magnet-based machines, hybrid excitation gives a variable flux while still using the advantage of the permanent magnets for a portion of the flux. This article also looks into some different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 200 publications
1
5
0
Order By: Relevance
“…Consequently, there is an increase in magnetic flux shunted from the permanent magnet to the pole claws, leading to a weakening of the magnetic flux Φδ entering the main air gap. These observations align with the analytical formulas (10) and (12).…”
Section: The Influence Of Permanent Magnet and Pole Claw Thickness On...supporting
confidence: 88%
See 1 more Smart Citation
“…Consequently, there is an increase in magnetic flux shunted from the permanent magnet to the pole claws, leading to a weakening of the magnetic flux Φδ entering the main air gap. These observations align with the analytical formulas (10) and (12).…”
Section: The Influence Of Permanent Magnet and Pole Claw Thickness On...supporting
confidence: 88%
“…Additionally, its external excitation capability allows for supplementary magnetic field adjustment when necessary, thus enhancing motor reliability. Presently, marine hybrid excitation motors have garnered significant attention from both domestic and international researchers [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Through 3-D finiteelement analysis, it is shown that a pole ratio of 8/1 offers higher torque density, machine efficiency, and fluxweakening capability compared to other ratios. Hybrid excitation motors, which integrate permanent magnet and field winding excitation techniques, are discussed in the paper [20]. Three categorization approaches, including reluctance circuit, excitation system location, and geometrical placement of excitation, are explored.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, researchers have conducted numerous studies aiming to maximize the output power per unit magnet volume [10]. One prevalent approach involves the modification of rotor structures [11][12][13]. Examples of such modifications include the utilization of a ferrite magnet-based interior PMSM [12] and of hybrid excitation motors [13].…”
Section: Introductionmentioning
confidence: 99%
“…One prevalent approach involves the modification of rotor structures [11][12][13]. Examples of such modifications include the utilization of a ferrite magnet-based interior PMSM [12] and of hybrid excitation motors [13]. These innovations demonstrate remarkable improvements in output power per unit magnet volume.…”
Section: Introductionmentioning
confidence: 99%